2022
DOI: 10.4269/ajtmh.20-1036
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Estimates of Acute Q Fever and Spotted Fever Group Rickettsioses, Kilimanjaro, Tanzania, from 2007 to 2008 and from 2012 to 2014

Abstract: Q fever and spotted fever group rickettsioses (SFGR) are common causes of severe febrile illness in northern Tanzania. Incidence estimates are needed to characterize the disease burden. Using hybrid surveillance—coupling case-finding at two referral hospitals and healthcare utilization data—we estimated the incidences of acute Q fever and SFGR in Moshi, Kilimanjaro, Tanzania, from 2007 to 2008 and from 2012 to 2014. Cases were defined as fever and a four-fold or greater increase in antibody titers of acute and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The majority of deaths occurred among those less than 50 years of age and due to non-malarial febrile illness. Rickettsial and viral aetiologies of severe febrile illness may represent an undetected and pervasive burden of disease [ 31 , 32 ]. Urgent surveillance efforts and field-ready clinical diagnostics are needed to identify treatable causes of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of deaths occurred among those less than 50 years of age and due to non-malarial febrile illness. Rickettsial and viral aetiologies of severe febrile illness may represent an undetected and pervasive burden of disease [ 31 , 32 ]. Urgent surveillance efforts and field-ready clinical diagnostics are needed to identify treatable causes of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere in sub-Saharan Africa, a study from Tanzania found 57 out of 641 (8.9%) patients with fever and paired serology had R . africae infection [ 9 ]. Rickettsial infections are a reality in sub-Saharan Africa, but the limited surveillance for nonmalarial febrile illnesses severely limits our understanding of the epidemiology and impact of diseases caused by R .…”
Section: Discussionmentioning
confidence: 99%
“…ATBF is a neglected disease that can cause illness in travelers and rural inhabitants bitten by ticks in endemic regions [ 4 , 8 , 9 ]. Rickettsial infections are second only to malaria as the cause of acute febrile illnesses among travelers to sub-Saharan Africa [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by a recent estimate of Q fever annual incidence in northern Tanzania of 80 cases per 100,000 persons. 11 The preponderance of Q fever cases in Europe, Australia, and North America could merely reflect greater availability of resources in these regions. Improvements in the availability of diagnostic testing, epidemiological expertise, and health-care provider education are all key components for a better understanding of Q fever in tropical areas.…”
mentioning
confidence: 99%